The Egyptian revival : ancient Egypt as the inspiration for design motifs in the west - Curl, James Stevens, 1937- (Routledge, 2005)
Professor Curl's magisterial survey is a definitive account of the ways in which artists and especially architects have brought Egyptian forms and images into the public eye.